2021
DOI: 10.1186/s13104-021-05591-y
|View full text |Cite
|
Sign up to set email alerts
|

Multiple myeloma and physical activity

Abstract: Objective Physical activity has been shown to improve quality of life in cancer patients with some evidence in multiple myeloma. This study aimed to determine myeloma patients’ exercise levels, their perception of physical activity, and to explore correlations with quality of life. Myeloma outpatients were invited to complete a number of questionnaires, including the Godin leisure-time exercise questionnaire (GLTEQ) to determine their exercise levels, the Functional Assessment of Cancer Therapy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 19 publications
1
18
0
Order By: Relevance
“…A notable outcome was the increase in physical activity post-PrISMS clinic, as evident in the significant increase in patients' GLTEQ scores. We have previously shown that the majority of MM patients have low GLTEQ scores [11], which is demonstrated again here in the low pre-PrISMS GLTEQ scores. This underlines the low levels of exercise in our patients, likely due to existing myeloma bone complications and the fear of exacerbating these when exercising.…”
Section: Discussionsupporting
confidence: 84%
See 4 more Smart Citations
“…A notable outcome was the increase in physical activity post-PrISMS clinic, as evident in the significant increase in patients' GLTEQ scores. We have previously shown that the majority of MM patients have low GLTEQ scores [11], which is demonstrated again here in the low pre-PrISMS GLTEQ scores. This underlines the low levels of exercise in our patients, likely due to existing myeloma bone complications and the fear of exacerbating these when exercising.…”
Section: Discussionsupporting
confidence: 84%
“…It has been shown to correlate significantly with social, functional, mental and sexual well-being, as well as lower pain and fatigue scores. We also demonstrated in our previous studies that higher exercise levels were associated with better QoL and that exercise intervention could improve muscle strength and cardiovascular fitness [ 9 11 ]. Moreover, the U.K.…”
Section: Discussionmentioning
confidence: 54%
See 3 more Smart Citations